Revisiting the Oxidation of Flavonoids: Loss, Conservation or Enhancement of Their Antioxidant Properties - Hernan Speisky; Fereidoon Shahidi; Adriano Costa de Camargo; Jocelyn Fuentes (MDPI AG, 2022)
Flavonoids display a broad range of health-promoting bioactivities. Among these, their capacity to act as antioxidants has remained most prominent. The canonical reactive oxygen species (ROS)-scavenging mode of the antioxidant action of flavonoids relies on the high susceptibility of their phenolic moieties to undergo oxidation. As a consequence, upon reaction with ROS, the antioxidant capacity of flavonoids is severely compromised. Other phenol-compromising reactions, such as those involved in the biotransformation of flavonoids, can also markedly affect their antioxidant properties. In recent years, however, increasing evidence has indicated that, at least for some flavonoids, the oxidation of such residues can in fact markedly enhance their original antioxidant properties. In such apparent paradoxical cases, the antioxidant activity arises from the pro-oxidant and/or electrophilic character of some of their oxidation-derived metabolites and is exerted by activating the Nrf2-Keap1 pathway, which upregulates the cell's endogenous antioxidant capacity, and/or, by preventing the activation of the pro-oxidant and pro-inflammatory NF-κB pathway. This review focuses on the effects that the oxidative and/or non-oxidative modification of the phenolic groups of flavonoids may have on the ability of the resulting metabolites to promote direct and/or indirect antioxidant actions. Considering the case of a metabolite resulting from the oxidation of quercetin, we offer a comprehensive description of the evidence that increasingly supports the concept that, in the case of certain flavonoids, the oxidation of phenolics emerges as a mechanism that markedly amplifies their original antioxidant properties. An overlooked topic of great phytomedicine potential is thus unraveled.